Pengaruh Pengetahuan, Pendapatan, dan Kepercayaan terhadap Minat Muzakki di Baznas Kota Malang - Mohammad Afandi; Ilfi Nur Diana; Nur Asnawi (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2023)
This study examines the effect of knowledge, income, and trust on interest in zakat Muzakki at Baznas Malang City. Zakat funds collected by the Malang City Baznas in 2019-2021 have increased. The Covid-19 conditions that occurred in that year did not cause a decrease in the collection of zakat funds but instead increased. This study used a quantitative method with a data search model using a questionnaire analyzed using the SPSS version 22 application. There were 100 respondents in this study. Based on this research test, each variable partially influences Muzakki's interest. The knowledge variable has a positive effect on Muzakki's interest, the income variable has a positive effect on muzakki's interest, and the trust variable has a positive effect on Muzakki's interest. Simultaneously this study found a positive influence of the three variables on Muzakki's interest in Baznas Malang City. With these results, this study recommends that amil zakat institutions and bodies always pay attention to Muslim knowledge about zakat and constantly improve institutional management to be transparent, open, and honest so the community can trust it.